The Effectiveness of Rapid Typing Software and Module for Improving 10-Finger Typing Skills - Ikhsananto, Aan; Sutirman, Sutirman (Dinamika Pendidikan, 2018)
This research aims to know the effectiveness of rapid typing software and module in improving students typing skills. The program of Automatic Expertise and Office Governance requires students to be able to master typing skills. The population of the study was 62 students of class X OTKP 1 and OTKP 2 in SMK N 7 Yogyakarta. Samples were 30 students of class X OTKP 2 and the class selection used simple random sampling technique. The data collection methods were text typing skills documentations and Multivariate Analysis of Variance (MANOVA) test method was used for the data analysis. The simultaneous test results show the significance of 0.000 < 0.05, it means all variables have a significant influence on typing skills. While the test results partially indicate that the rapid typing software and module only have a significant influence on the sub competence of typing speed, but no impact on the accuracy of typing. Based on these findings it can be concluded that rapid typing software and modules have a significant and effective influence in improving typing skills. Rapid typing software cannot only be used in schools but can also be applied in offices, government agencies and private sectors.